How Low-Carbon Issues are Addressed in Primary School Textbooks - Hudha, M. N.; Hamidah, I.; Permanasari, A.; Abdullah, A. G. (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to examine the existence of learning material related to educational issues regarding low-carbon levels. Through the content analysis, 26 primary school science textbooks from ten publishers in Indonesia were reviewed, focusing on the study covering the selection, presentation, provision of supporting materials, and low-carbon issues. The research method used is the qualitative content analysis process method with research steps: 1) Data collection; 2) Data analysis textbook; and 3) Ethical considerations. The results showed that sixty one point six percent of teachers said the book was under the curriculum's coverage. The sixty point six percent of the relevance of content to student experiences was appropriate, so is the fifty three point five percent of the relevance of examples and exercises with learning objectives and the material presented. It is also found that fifty five point six percent of various questions and discussions were adequate for testing students, the other fifty one point five percent had included supporting questions and exercises, and sixty point six percent of teachers said there was a teacher's guide. Then fifty point five percent, according to the teacher, students' awareness of low carbon is still relatively low, and forty six point six percent of the content coverage regarding low carbon is still considered sufficient by the teacher. This study concludes that there was too little coverage of low-carbon issues and a lack of additional material related to the low-carbon content in primary science textbooks. The topic of low carbon is still implicit in the environmental literacy found in textbooks. The follow-up that can be done is providing a low-carbon concept to science textbooks in primary schools so that our students and society will have low-carbon awareness and increased environmental literacy.